Resilience as a Mediator of the Relationship between Stress Levels and Adaptive Performance in the Outer Islands TNI-AL (Indonesian National Army Navy) - Bantam, Dian Juliarti; Yanto, Agus Dwi; Syach, Muhammad Erwan (Universitas Muhammadiyah Metro, 2021)
This research aims to test the relationship between stress level and adaptive performance TNI-AL (Indonesian National Army Navy) and the impact of resilience as a moderator variable. The measures applied a 4‐point scale response ranging from 1 (very inappropriate or strongly disagree) to 4 (very suitable or strongly agree). Respondents were 71 TNI-AL assigned to the Outer Islands of Indonesia. This research uses a quantitative method with Moderated Regression Analysis technique (MRA) for data analysis. The analysis results show a B value of -1.104 and a significance value of 0.000 (p<0.05), which means a negative relationship between stress level and adaptive performance. Meanwhile, the moderator variable shows a significance value of 0.904 (p>0.05), which means that the resilience variable cannot explain the relationship between stress levels and adaptive performance of TNI-AL assigned to the Outer Islands of Indonesia.